RESEÑA de: Constantinesco, Vlad (ed.). "Europe et souveraineté = Europe and sovereignty". Número 368 de la Revista "L’Europe en formation", 2013. - Torres Gutiérrez, Alejandro (Teoría y Realidad Constitucional, 2014)
-